Способ получения нефтеполимерных смол - Бондалетов В. Г. Владимир Григорьевич; Фитерер Е. П. Елена Петровна; Ионова Е. И. Елена Ивановна; Бондалетов О. В. Олег Владимирович; Толмачева В. Я. Валентина Яковлевна
опубл. 27.07.10